Toward Normative Expert Systems: Part II Probability-Based Representations for Efficient Knowledge Acquisition and Inference - Heckerman, E. D.; Nathwani, N. B. (Methods of Information in Medicine, 1992)
We address practical issues concerning the construction and use of decision-theoretic or normative expert systems for diagnosis. In particular, we examine Pathfinder, a normative expert system that assists surgical pathologists with the diagnosis of lymph-node diseases, and discuss the representation of dependencies among pieces of evidence within this system. We describe the belief network, a graphical representation of probabilistic dependencies. We see how Pathfinder uses a belief network to construct differential diagnosis efficiently, even when there are dependencies among pieces of evidence. In addition, we introduce an extension of the belief-network representation called a similarity network, a tool for constructing large and complex belief networks. The representation allows a user to construct independent belief networks for subsets of a given domain. A valid belief network for the entire domain can then be constructed from the individual belief networks. We also introduce the partition, a graphical representation that facilitates the assessment of probabilities associated with a belief network. We show that the similarity-network and partition representations made practical the construction of Pathfinder.
Keywords: Expert Systems; Diagnosis; Probability Theory; Decision Theory; Artificial Intelligence; Belief Networks; Similarity Networks; Partitions; Pathology